Time series video analysis of bubble release processes at natural hydrocarbon seeps in the Northern Gulf of Mexico. (April 2017) - Johansen, Caroline; Todd, Austin C.; MacDonald, Ian R.
Abstract: This research quantifies the rate and volume of oil and gas released from two natural seep sites in the Gulf of Mexico: lease blocks GC600 (1200 m depth) and MC118 (850 m depth). Our objectives were to determine variability in release rates and bubble size at five individual vents and to investigate the effects of tidal fluctuations on bubble release. Observations with autonomous video cameras captured the formation of individual bubbles as they were released through partially exposed deposits of gas hydrate. Image processing techniques determined bubble type (oily, gaseous, and mixed: oily and gaseous), size distribution, release rate, and temporal variations (observation intervals ranged from 3 h to 26 d). A semi-automatic bubble counting algorithm was developed to analyze bubble count and release rates from video data. This method is suitable for discrete vents with small bubble streams commonly seen at seeps and is adaptable to multiple in situ set-ups. Two vents at GC600 (Birthday Candles 1 and Birthday Candles 2) were analyzed. They released oily bubbles with an average diameter of 5.0 mm at a rate of 4.7 bubbles s −1, and 1.3 bubbles s −1, respectively. Approximately 1 km away, within the GC600 seep site, two more vents (Mega Plume 1 and Mega Plume 2) were analyzed. These vents released a mixture of oily and gaseous bubbles with an average diameter of 3.9 mm at a rate of 49 bubbles s −1, and 81 bubbles s −1, respectively. The fifth vent at MC118 (Rudyville) released gaseous bubbles with an average diameter of 3.0 mm at a rate of 127 bubbles s −1 . Pressure records at Mega Plume and Rudyville showed a diurnal tidal cycle (24.5 h). Rudyville was the only vent that demonstrated any positive correlation (ρ = 0.60) to the 24.5 h diurnal tidal cycle. However, these observations were not conclusive regarding tidal effects on bubble release. Highlights: Autonomous camera system to monitor oil and gas bubble release. Semi-automatic bubble counting algorithm. Time series of bubble release rates ranging from 3 h to 26 days. Bubble size distribution.